Prevalence and Factors Affecting Metabolic Syndrome in Burmese Type 2 Diabetic Patients in Thailand: A Single-Center, Cross-Sectional Study - Khin, May Myat Thwe; Choppradit, Chanchira; Meksawan, Kulwara (Journal of Basic and Applied Pharmacology, 2024)
Nowadays, the prevalence of metabolic syndrome (MetS) is increasing worldwide, and it was also found among type 2 diabetic patients. The objective of this study was to investigate the prevalence and factors affecting MetS in Burmese type 2 diabetic patients by using two different MetS criteria. In this cross-sectional study, information on general characteristics, anthropometry, laboratory parameters, and dietary intake was collected from Burmese patients with type 2 diabetes at Samutsakhon Hospital, Samut Sakhon Province, Thailand. The prevalence and factors affecting MetS were determined. The prevalence of MetS was 78.1% and 67.2% according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) and the International Diabetes Federation (IDF) criteria, respectively. According to the NCEP ATP III criteria, comorbid diseases (AOR: 3.96, 95%CI: 1.75-8.94) and time spent sitting >3 hours on a typical day (AOR: 5.40, 95%CI: 1.66-17.62) affected MetS. Based on the IDF criteria, the factors influencing MetS were female (AOR: 3.06, 95%CI: 1.31-7.19), comorbid diseases (AOR: 2.62, 95%CI: 1.27-5.41) and time spent sitting >3 hours on a typical day (AOR: 3.83, 95%CI: 1.29-11.35). Participants with MetS consumed more energy and all macronutrients than those without MetS (all p<0.05). The results of this study indicate the high prevalence of MetS in Burmese type 2 diabetic patients. Several factors affect MetS and these should be taken into consideration to develop strategies for prevention and management of MetS and type 2 diabetes in these patients.